Desert dust improves the photophysiology of heat-stressed corals beyond iron - Katherine Amorim; R. Grover; D. Omanović; L. Sauzéat; M. I. Marcus Do Noscimiento; Maoz Fine; Christine Ferrier-Pagès (Scientific Reports)
Abstract Desert dust is an important source of essential metals for marine primary productivity, especially in oligotrophic systems surrounded by deserts, such as the Red Sea. However, there are very few studies on the effects of dust on reef-building corals and none on the response of corals to heat stress. We therefore supplied dust to two coral species (Stylophora pistillata and Turbinaria reniformis) kept under control conditions (26 °C) or heat stress (32 °C). Since dust releases large amounts of iron (Fe) in seawater, among other metals, the direct effect of different forms of Fe enrichment on coral photosynthesis was also tested. First, our results show that the desert dust altered the coral metallome by increasing the content of metals that are important for coral physiology (e.g. lithium (up to 5-fold), manganese (up to 4-fold in S. pistillata), iron (up to 3-fold in S. pistillata), magnesium (up to 1.3-fold), molybdenum (up to 1.5-fold in S. pistillata)). Overall, metal enrichment improved the photosynthetic performance of corals, especially under thermal stress (e.g. Pgross (up to 2-fold), Pnet (up to 10-fold), chlorophyll (up to 1.5-fold), symbionts (up to 1.6-fold)). However, Fe exposure (ferric chloride or ferric citrate) did not directly improve photosynthesis, suggesting that it is the combination of metals released by the dust, the so-called “metal cocktail effect”, that has a positive impact on coral photophysiology. Dust also led to a decrease in Ni uptake (up to 1.4-fold in the symbionts), likely related to the nitrogen metabolism. Finally, we found that the isotopic signature of metals such as iron, zinc and copper is a good indicator of heat stress and dust exposure in corals. In conclusion, desert dust can increase coral resistance to bleaching by supplying corals with essential metals.